Convergence and Potential Economic Development in the Special Region of Yogyakarta - Yustirania Septiani (EKO-REGIONAL, 2019)
This study aims to determine whether there is a lag between a region with another, to determine whether the regions with low income will be able to catch up with regions with higher income. The objectives of this study are to analyze the convergence that might occur in Yogyakarta and analyze the potential economic sectors in economic development in Yogyakarta. This study used panel secondary data, the data were obtained from 5 regions in Yogyakarta from 2010-2015. The methods were panel data regression, location quotient, dynamic location quotient, and shift share. The result showed that there was no convergence, but there was divergence, and competitive and specialized sectors in regencies / cities in Yogyakarta were agricultural, forestry, and fishing sector, mining and excavation sector, processing industry sector, procurement of electricity and gas sector, water supply, waste management and recycling sector, construction sector, and transportation and trade sector.Keywords: Convergence, Potential Sector, Economic Development.